The Weak Messianic Force of Improvisation. For a New Paradigm of Acting (Itinera, 2015)
The themes of improvisation and of unfulfillment share many traits. Both take a stand against the «absolute norm» imposed by the technocratic consumer society; both re-explore discarded options in search for a brand new solution. Accordingly, action (including political action) must be reconsidered in light of the theme of reversibility, what Italo Calvino and Michelangelo have shown us about the process of artistic creation. Further confirmation of this is offered by Luigi Pareyson’s theory of formativity.